2018
DOI: 10.18865/ed.28.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Mental Health, and Quality of Life am ong Hispanic Childhood Cancer Survivors: A Latent Class Analysis

Abstract: The assimilated group had significantly more depressive symptoms and lower quality of life than the other two groups. This may indicate that loss of the Hispanic culture may be associated with poorer psychosocial health among CCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…For example, research suggests that biculturalism tends to be associated with mental health well-being among US minority individuals, such as a positive correlation with self-esteem 84 and negative correlation with depression symptoms. 85 Given these methodological challenges, it is unsurprising that research on thin-ideal internalization, eating pathology, and acculturation is so mixed and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research suggests that biculturalism tends to be associated with mental health well-being among US minority individuals, such as a positive correlation with self-esteem 84 and negative correlation with depression symptoms. 85 Given these methodological challenges, it is unsurprising that research on thin-ideal internalization, eating pathology, and acculturation is so mixed and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study among cervical cancer survivors reported no differences in overall HRQOL between Hispanics/Latinas and non-Hispanics/Latinas [73]. In terms of correlates of HRQOL, greater acculturation, shame, and stigma were negatively associated with overall HRQOL, while more physical activity, inner peace, and better physical, social, psychological and functional well-being were positively associated with overall HRQOL among Hispanic/Latino cancer survivors [6,57,75,110,144,163,[166][167][168].…”
Section: Combined "Overall" Hrqolmentioning
confidence: 97%
“…In contrast, a study examining HRQOL among cervical cancer survivors found no differences in rates of depression between Hispanics/Latinas and non-Hispanic/Latina survivors [73]. Several factors were associated with increased risk for depression among Hispanic/Latino cancer survivors, including lower education, poor physical/social functioning, less social (e.g., family, peer) and emotional support, higher stress, poor body image, poor coping, self-blame, and Spanish language preference [57,70,74,75].…”
Section: Psychological Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural beliefs (i.e. fatalism) and gender beliefs seem relevant to health disparities in non-Hispanic Black survivors (26), while family dynamics, such as foreign-born parents experiencing greater amounts of post-traumatic stress, may impact Hispanic survivors (34,59). In addition, minority childhood cancer survivors who had better social skills (27) and post-traumatic growth (31) were associated with better health outcomes.…”
Section: Racial/ethnic Disparity-specific Interventionsmentioning
confidence: 99%